Design analysis of a hybrid jet-pump CO2 compression system - Worall, Mark; Omer, Siddig; Riffat, Saffa (2010)
Transport refrigeration contributes to anthropogenic global warming directly because of leakage of refrigerant, usually using high global warming potential (GWP) refrigerants, and indirectly because of the greenhouse gases emitted in driving the vehicle and the refrigeration system. A hybrid jet-pump CO2 compression system is being designed for transport refrigeration so that the GWP of the system is reduced and its performance improved. The jet-pump utilises waste heat from the exhaust gases of the engine to subcool the refrigerant and so enhance performance, reduce energy required from the engine and minimise GWP of the system. The hybrid jet-pump CO2 compression system has been simulated and its performance determined for different operating conditions and optimised using entropy generation minimisation. At an evaporator temperature of -18°C, an ambient temperature of 35°C and a generator temperature of 120°C, the COP increases from about 1.0 to 2.27 as the degree of subcooling increases from 0K to 20K. Similarly, compressor work is reduced by 24% at 20K subcooling. The optimum degree of subcooling was approximately 10K for the operating conditions described above. An improved COP is achieved whilst the size of heat exchangers required to operate the jet-pump are minimised with respect to the overall weight of the system and thus its impact on indirect emissions.